Collaboration and community of practice in online social networking services among Malaysian university students - Afendi Hamat,; Haslinda Abu Hassan,; Mohamed Amin Embi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article reports the results of an exploratory study to investigate the usage patterns of social networking services (SNS) by Malaysian tertiary level students. The focus in this paper is on the collaborative use of SNS including the factors (variables of level of study, gender and academic performance) that might have influenced how SNS is used by Malaysian students. This focus is necessary as so far, no research have looked at these variables across the population of Malaysian university students. An online survey was carried out using convenience sampling and this returned a usable result set of N=16661. Frequency analysis revealed that 68.6% of respondents used SNS to collaborate with their peers, and more than half join study groups on SNS (57.5%) as well as course groups created by their lecturers (56.1%) at a high level of frequency; many reported using SNSs often/all the time for these purposes. Further analysis showed statistical significance for almost all the variables investigated. However, results of Cohen’s effect size indicated that the differences between the Postgraduate-Undergraduate variable pairs (Collaboration d = 0.27 and Community of Practice d = 0.24) have a small to moderate practical significance which may be meaningful. The findings suggest that the practical and pedagogical differences between undergraduate and postgraduate levels of study should be given due consideration when integrating the use of SNS into higher education in Malaysia.